From understanding to insight: using reflexivity to promote students' learning of qualitative research. Issue 2 (3rd March 2016) - Goldblatt, Hadass; Band-Winterstein, Tova
Abstract: Reflexivity is qualitative researchers' thoughtful and self-aware examination of the intersubjective dynamics between themselves and study participants, evoking insightful understanding of others. Novice qualitative researchers need to acquire reflexive skills for their professional development. In this article, we examine reflexivity among Israeli students on a qualitative research course. We conducted thematic content analysis of the data gathered from the students' written reflexive journals. Reflexivity was demonstrated by three dimensions in each stage of the students' experience of learning qualitative research: (1) 'I as a person', relating to students' critical personal perspective; (2) 'I as a researcher', referring to the students' insights about their evolving competencies as researchers; and (3) 'I as an individual in a sociocultural context', stressing students' awareness of their values, beliefs and norms. These findings are discussed, highlighting four key concepts in qualitative research: Taken-for-Granted Expectations; Experience of Discovery; Resonance, and Meaning Making and Insights.